Pengaruh Stres Kerja, Motivasi Kerja, Kompensasi terhadap Kinerja Karyawan Dengan Lama Kerja Sebagai Variabel Moderating - Anik Irawati (Akuntabilitas, 2018)
This research was conducted to prove empirically the effect of the work stress, the work motivation, the compensation on the employee performance using the working time as the moderating variable. The population in this research was the banking companies employees in Bandar Lampung. The data used in this research was the primary data. The sampling technique used convenience sampling. The independent variables used were the work stress, employee motivation, and compensation. The dependent variable used was the employee performance. The moderating variable was working time. The number of questionnaires used was 26 questionnaires. The data analysis technique used was multiple linear regression. The result of this research showed that the work stress and the work motivation affected the employee performance. Moreover, the compensation did not affect the employee performance. In addition, the working time was not able to moderate the effect of the work stress, the employee motivation, and the compensation on the employee performance